2022
DOI: 10.1111/desc.13229
|View full text |Cite
|
Sign up to set email alerts
|

To snack or not to snack: Using fNIRS to link inhibitory control to functional connectivity in the toddler brain

Abstract: Inhibitory control (IC) emerges in infancy, continues to develop throughout childhood and is linked to later life outcomes such as school achievement, prosocial behavior, and psychopathology. Little, however, is known about the neural processes underpinning IC, especially in 2-year-olds. In this study, we examine functional connectivity (FC) in 2.5-year-olds while recording hemodynamic responses via functional infrared spectroscopy (fNIRS) during a traditional snack delay task. We found that functional connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(88 reference statements)
1
2
0
Order By: Relevance
“…The increasing involvement of both hemispheres during an IC task across this age range suggests that greater functional connectivity within and between frontal and parietal regions may support the development of IC. This is further supported by another fNIRS study that showed that 2½-year-old toddlers who performed better in a snack delay task had stronger functional connections between left and right parietal cortices, and between frontal and parietal cortices (Kerr-German et al, 2022).…”
Section: Fig 3 Functional Near-infrared Spectroscopy (Fnirs) Is a Neu...supporting
confidence: 58%
“…The increasing involvement of both hemispheres during an IC task across this age range suggests that greater functional connectivity within and between frontal and parietal regions may support the development of IC. This is further supported by another fNIRS study that showed that 2½-year-old toddlers who performed better in a snack delay task had stronger functional connections between left and right parietal cortices, and between frontal and parietal cortices (Kerr-German et al, 2022).…”
Section: Fig 3 Functional Near-infrared Spectroscopy (Fnirs) Is a Neu...supporting
confidence: 58%
“…In practice, functional connectivity can be examined whilst at rest (resting state functional connectivity, e.g., Bulgarelli et al, 2019), and so capturing the correlations between spontaneous fluctuations in neural activity in the absence of a task. It can also be examined whilst a participant is completing a task (i.e., task-based functional connectivity, e.g., Kerr-German et al, 2022), and so measuring correlated neural activity that is modulated based on explicitly presented cognitive demands. There are a number of analytic approaches to task-based functional connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of fNIRS to measure resting state functional connectivity in infant populations has been consistently demonstrated across the last two decades (Bulgarelli et al, 2024;Hu et al, 2020;Lu et al, 2010). There is also substantial promise for task-based functional connectivity using fNIRS in the first two years of life (Keehn et al, 2013;Kerr-German et al, 2022;Naoi et al, 2013Naoi et al, , 2022, although currently research is limited in comparison to adult resting state fNIRS studies. This difference may be attributed to the existing difficulties surrounding infant fNIRS data collection (see Baek et al 2023 for a comprehensive discussion), as well as the general challenges of working with infant participants.…”
Section: Introductionmentioning
confidence: 99%